2000
DOI: 10.1086/315748
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Human Immunodeficiency Virus Type 1–Specific CD4 and CD8 T Cell Responses in Chronically Infected Persons after Temporary Treatment Interruption

Abstract: Immunologic and virologic outcomes of treatment interruption were compared for 5 chronically human immunodeficiency virus (HIV)-infected persons who have maintained antiretroviral therapy-mediated virus suppression, as compared with 5 untreated controls. After a median interruption of 55 days of therapy accompanied by rebound of virus, reinitiated therapy in 4 of 5 subjects resulted in suppression of 98.86% of plasma virus load by 21-33 days and no significant decrease in CD4 T cell percentage from baseline. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 53 publications
(53 reference statements)
4
55
2
Order By: Relevance
“…After the cessation of therapy, HIV p24-specific CD4 ϩ T cell frequencies were not maintained in the group with the higher pretreatment VL. Such transient increases in HIV-specific CD4 ϩ T cell responses have also been described in other studies of STI (21,24,34,35). This result is in contrast to the patient group with lower pretreatment VL who maintained, and even increased, levels of HIV p24-specific CD4 ϩ T cells after the cessation of therapy.…”
Section: Lack Of Correlation Between Plateau Vl and Magnitude Of Hiv-supporting
confidence: 71%
“…After the cessation of therapy, HIV p24-specific CD4 ϩ T cell frequencies were not maintained in the group with the higher pretreatment VL. Such transient increases in HIV-specific CD4 ϩ T cell responses have also been described in other studies of STI (21,24,34,35). This result is in contrast to the patient group with lower pretreatment VL who maintained, and even increased, levels of HIV p24-specific CD4 ϩ T cells after the cessation of therapy.…”
Section: Lack Of Correlation Between Plateau Vl and Magnitude Of Hiv-supporting
confidence: 71%
“…Blood samples were obtained on days 0, 4,8,14,18,22,24,28,35,42,56, and 70 of each cycle; every week from week 40 to 52; and every 1 to 2 weeks to week 64. Blood was processed within 2 h after blood was drawn.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, strategies to decrease viral set points are warranted. Recent studies suggested that this viral set point might be lowered in HIV-infected individuals by structured treatment interruptions (STIs), in which antiretroviral therapy (ART) is transiently and repeatedly discontinued with the aim of "autovaccinating" the individual through controlled exposure to autologous virus (8,12,23,24,28,33). A decrease in viral growth kinetics over three treatment interruptions has been reported in some patients and was paralleled by increasing HIV-specific…”
mentioning
confidence: 99%
“…Opportunistic Infect.). Furthermore, while there was a correlation between reductions in plasma HIV RNA levels from cycle to cycle and enhanced HIV-specific immune responses in certain reports (34,37), other studies have failed to observe an immunologic benefit of treatment interruptions (32; Hirschel et al, 9th Conf. Retrovir.…”
Section: Various Strategies Of Interrupting Highly Active Antiretrovimentioning
confidence: 99%